Gamified Coding: Toy Robots and Playful Learning in Early Education - Heljakka Katriina; Ihamäki Pirita; Tuomi Pauliina; Saarikoski Petri (United States, 2022)
This paper explores the activity of coding with smart toy robots Dash and Botley as a part of playful learning in the Furnish early education context. The findings of our study demonstrate how coding with the two toy robots was approached, conducted and played by Finnish preschoolers aged 5-6 years. The main conclusion of the study is that preschoolers used the toy robots with affordances related to coding mainly in developing gamified play around them by designing tracks for the toys, programming the toys to solve obstacle paths, and competing in player-generated contests of dexterity, speed and physically mobile play.
Proceedings 2019 International Conference on Computational Science and Computational Intelligence